Study of outcome of the treatment with intravenous iron sucrose in moderately anaemic pregnant women - Kalimuthu, Kohila; Avudaithangam, Vanusha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Moderate anaemia seen in about 15-20% of pregnant women. Iron sucrose complex which is used intravenously for the correction of Iron deficiency anaemia. The drug has been able to raise the haemoglobin to satisfactory level when used in moderately anaemic iron deficient pregnant women. The objective of this study was to study the improvement of Hb% after treatment with intravenous Iron sucrose complex in moderately anaemic pregnant women belonging to 24-32 weeks of gestational age. Methods: 50 antenatal patients between gestational age 24-32 weeks with hemoglobin between 8-9.5g/dl were selected and included in this study. They were subjected to blood hemoglobin estimation, hematocrit and peripheral smear study. In each infusion, the maximum total dose administered was 200 mg iron sucrose in 100 ml of normal saline, slow IV infused over 30 minutes. Monitoring was done throughout the infusion to observe for any side effects. Results: Mean hemoglobin among the 50 patients before starting the therapy was 8.172g/dl and the mean hemoglobin at the end of one month of completing the therapy was 11.066g/dl. The rise in mean hemoglobin i.e. the difference in the mean hemoglobin before and after treatment was 2.894g/dl. The p value is 0.0001 which is statistically significant. The mean hematocrit of the 50 patients studied before starting the treatment was 26.772% with a standard deviation of 1.914. The mean hematocrit after completing the therapy was 33.872% with a standard deviation of 1.321. The difference in the mean hematocrit was 7.100% with a p value of 0.0001 which is statistically significant. Conclusions: Intravenous iron sucrose complex is well tolerated and highly efficacious in improving hemoglobin, hematocrit in the treatment of iron deficiency anaemia in antenatal women.